Efektivitas Badan Usaha Milik Desa (BUMDes) dalam meningkatkan kesejahteraan masyarakat - Ikhsan, Luthfi Ridhatul; Priatna, Wahyu Budi; Burhanuddin, Burhanuddin (Universitas Widya Mataram, 2024)
Development that starts in the village sector is the first step to run the economy of Indonesia, one of the many development programmes are the formation of the Village-Owned Enterprise (BUMDes). The presence of BUMDes is expected to be able to improve the standard of living and community welfare. Community welfare itself has a meaning that has been stated in Indonesian Law (UU No. 11 of 2009). The objectives of this study are to analyze the effectiveness of Village-Owned Enterprises that have managed their business units, to analyze the welfare of village communities affected by the operation of Village-Owned Enterprises and to analyze the influence that occurs between the effectiveness of Village-Owned Enterprises and the welfare of village communities. Descriptive analysis, paired sample T-Test, correlation and ordinal regression analysis are among those of the methode that are used in this study. The result of the study shows that there is a positive and significant correlation between the effectivity of the BUMDes and the welfare of the villagers, and there are 4 indicators of effectiveness of the BUMDes that significantly impactful to the welfare of the villagers, and it consist of sustainability, impact, empowerment, and participation.